Cassava pest in retreat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The battle against the cassava green mite (Mononychellus tanajoa) has turned and the pest is in retreat. After 13 years ofpainstaking research scientists are confident they have found the right natural enemies to control the pest. In 1971, cassava...